1998
DOI: 10.1063/1.367954
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-domain analysis of primary and secondary dielectric relaxation phenomena in a nonlinear optical side-chain polymer

Abstract: The investigation of dipole relaxation processes in nonlinear optical ͑NLO͒ polymers containing chromophore dipoles with large hyperpolarizabilities is important for optimizing the poling process and for predicting the long-term stability of the poling-induced order. The primary or ␣ relaxation is difficult to assess by dielectric spectroscopy in polymers with high glass transition temperature due to thermally induced chromophore degradation. A fast experimental procedure is developed for the investigation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…It is found that the parameters describing the distribution of relaxation times for most amorphous polymers change very little with temperature. 4 Thus, the temperature dependence of the effective relaxation time is a key parameter to characterize the temperature dependence of the relaxation process. Therefore, the activation energy (effective relaxation time) and characteristic transition temperature (T g ) for each process of a polymer are widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the parameters describing the distribution of relaxation times for most amorphous polymers change very little with temperature. 4 Thus, the temperature dependence of the effective relaxation time is a key parameter to characterize the temperature dependence of the relaxation process. Therefore, the activation energy (effective relaxation time) and characteristic transition temperature (T g ) for each process of a polymer are widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the fact that some relaxation of local stresses accumulated by sample preparation would cause the randomization of aligned NLO dyes, leading to depression of NLO activity. Cheng et al have reported the primary and secondary dielectric relaxation phenomena in an NLO polymer [50]. It was found that dielectric measurements on a typical NLO sidechain polymer exhibited multiple relaxation processes even below room temperature, which are all related to the chemically attached chromophore dipoles.…”
Section: As Shown Inmentioning
confidence: 97%
“…With a dye loading of 90 mol%, the P(S-MA)-DR1 side-chain polymer showed a glass-transition temperature T g = 137°C, as measured with DSC at the same heating rate of 10°C/min [10]. After thermally poling the polymers for 10 min 20°C above their respective glass-transition temperature with a poling field of 80 V/lm, stable, non-resonant electro-optical coefficients r 33 = 1.8 pm/V @ 1.55 lm and r 33 = 8.5 pm/V @ 1.55 lm were achieved for the guest-host [12] and the side-chain polymer, respectively [13].…”
Section: Sample Preparationmentioning
confidence: 99%